PENGEMBANGAN SISTEM INFORMASI MONITORING HARIAN MAGANG INDUSTRI PENDIDIKAN TEKNIK MESIN MENGGUNAKAN MODEL 4D - Sidik, Rasyid; Nurul Husnaini, Azizah; Syivarulli, Riina; Kholil, Muhammad; Rohman, Ngatou; Susilo Wijayanto, Danar (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2025)
The problems encountered in the industrial internship courses that are held conventionally are less actual daily log book recording and limited frequency of monitoring supervisors, resulting in less than optimal internship results. This research aims to develop a daily monitoring information system for industrial internships for Mechanical Engineering Education students at Sebelas Maret University. The research method used is Research and Development (RnD) with 4D models including Define, Design, Develop, and Disseminate. The result of this study is to develop a web-based daily monitoring information system for industrial internships and accommodate the industrial internship process from the preparation stage to the end of the assessment. Based on the analysis results, this information system obtained the